2008
DOI: 10.1186/1471-2164-9-383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of expressed sequence tags from a full-length enriched cDNA library of Cryptomeria japonica male strobili

Abstract: Background: Cryptomeria japonica D. Don is one of the most commercially important conifers in Japan. However, the allergic disease caused by its pollen is a severe public health problem in Japan. Since large-scale analysis of expressed sequence tags (ESTs) in the male strobili of C. japonica should help us to clarify the overall expression of genes during the process of pollen development, we constructed a full-length enriched cDNA library that was derived from male strobili at various developmental stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 67 publications
(73 reference statements)
4
41
0
1
Order By: Relevance
“…These observations showed that there were very few tissue-specific transcripts. Although Futamura et al (2008) reported the construction of a full-length cDNA library of the male strobilus of C. japonica and globally characterized expressed genes, many of the genes they isolated may not show male strobilus-specific expression. Moreover, the gene profiling associated with each developmental stage of the male strobilus of C. japonica has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations showed that there were very few tissue-specific transcripts. Although Futamura et al (2008) reported the construction of a full-length cDNA library of the male strobilus of C. japonica and globally characterized expressed genes, many of the genes they isolated may not show male strobilus-specific expression. Moreover, the gene profiling associated with each developmental stage of the male strobilus of C. japonica has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Global analyses of the expressed genes in mature pollen and the male strobilus of C. japonica have been reported by Futamura et al (2006Futamura et al ( , 2008. However, no profiling data are available of gene expression that is associated with different developmental stages of the male strobilus or pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Protein-coding sequences for T. distichum, C. japonica and Chamaecyparis obtusa We used 3,976 contig sequences from T. distichum and 32,167 complete cDNA sequences from C. japonica obtained from a Sugi genome database (Futamura et al, 2008). We used Chamaecyparis obtusa (Siebold & Zucc.)…”
Section: Methodsmentioning
confidence: 99%
“…Taxodium and Cryptomeria belong to the same subfamily, Taxodioideae, and these genera diverged roughly 90 million years ago (MYA) (Aulenback and LePage, 1998;Leslie et al, 2012). Recently, partial sequences of more than thirty thousand complete cDNAs of C. japonica have been released (Futamura et al, 2008). To analyze the rate and pattern of nucleotide substitutions between the Taxodium and Cryptomeria lineages, we determined cDNA sequences from T. distichum using next-generation sequencing (NGS) technology.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, approximately 20 % of adults suffer from C. japonica and Chamaecyparis obtusa pollinosis (Okuda 2003), which has become a serious health problem. Many studies have been performed on the flowering of C. japonica, such as histological analysis (Hashizume 1962), estimation of clonal variation of flower production (Saito and Kawasaki 1984), and recently, genetic analysis including establishment of cDNA or expressed sequence tag libraries (Futamura et al 2008;Kurita et al 2011) from male reproductive organs.…”
Section: Introductionmentioning
confidence: 99%